From popularization to marketization: The Hypermodal Nucleus in Institutional Science News - Zhang, Y.; O'Halloran, Kay (Routledge Taylor & Francis Group, 2013)
As digital technologies rapidly evolve, they change how information is presented, transmitted and shared, and concomitantly the ways in which semiotic resources (eg, language, images, and hyperlinks) are used to construe meaning. While digital media is having a pervasive impact on the way science news is presented (Trench, 2007,2008), the studies of online science news, however, are relatively rare compared to other types of online discourses (eg., Djonov, 2008; Knowx, 2007, 2009a; Tan, 2011; Zhang & O'Halloran, 2012) despite growing concerns about the nature of science journalism today.